Alfalfa Cost-Return Budget in South Central and Southeast Kansas - Fogleman, Sarah L.; Warmann, Gerald W. (My University, 1999)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in south central and southeast Kansas.
MF363_1999_10
Keywords: MF363; Economics; Crops; MF